Four Years Integrated Teacher Education Programme (ITEP): Issues & Concerns - Bharati, Ganiger (Voices of Teachers and Teacher Educators, 2019)
The globe is in quest of Quality Education. Quality education is expected to come from quality teachers; Quality Teacher is the expected outcome of the Teacher Education Program. There is a dire need of quality teacher education programmes in India. Accordingly the National Council for Teacher Education has kept on striving to bring reforms in Teacher Education. The content and structure of teacher education is continuously undergoing changes. It has been trying reform practices, such as, Personalized Teacher Education”, “Wholistic Teacher Education”,“Integrated Teacher Education”, “Dedicated Teacher Education”. Presently there is buzz on four years integrated teacher education programmes, that has evolved with the attempt to bring quality teacher education in India. The present article tries to focus on the modalities, issues and concerns regarding ITEP